Social Media Acceptability among Ulama in Ogan Ilir District, South Sumatra, Indonesia - Mery Yanti; Yusnaini Yusnaini (Jurnal Pendidikan Islam Indonesia, 2021)
Social media was born as a derivative of information and communication technology (ICT) development. It is stimulating new habits for people to produce, consumption, and distribution information in online interaction. Although many researchers have studied social media, no one has provided attention to social media and ulama (Islamic scholar). This article aims to describe patterns of ownership, access, perceived usefulness, and ease of use of social media among ulama. Based on qualitative research in Ogan Ilir District, South Sumatera Province, we found that the acceptability of social media among ulama in Ogan Ilir District is positive. Online life has become the new identity of ulama in this area. They use social media for broadcasting da’wah message and selling or buying goods and service. However, no ulama are producing their messages of da'wah. Facebook is the most popular social media among ulama. We also find that feeling safe and comfortable, get the real benefits from social media, network quality, and jihad in cyberspace have positive contributions to social media adoption within ulama. We identify the availability of time, audience response, negative content, addictive situations, and internet cost as the inhibiting factor of social media adoption among ulama. We discussed these findings and suggested practical recommendations and agenda for further research.